Isoform-specific functions of the dystonin cytoskeletal organizing proteins - Young, Kevin G (University of Ottawa (Canada), 2007)
Dystonin/Bpag 1 proteins, whose loss of function results in neuromuscular dysfunction in mice, have been implicated as being essential cytoskeletal organizing proteins in sensory neurons. How exactly they function as such is unclear, however. I have attempted to characterize the subcellular localizations and interactions of different dystonin isoforms in order to help place these proteins into their relevant cellular contexts. By using fusion protein analysis and observing the localization of endogenous dystonin in tissue culture cells, I have determined that the dystonin-a2 isoform can insert into internal membranes around the nucleus via an N-terminal transmembrane domain. Subsequently I demonstrated that a full-length dystonin-a2 fusion protein can reorganize the endoplasmic reticulum (ER) and associate with an outer nuclear membrane protein. The dystonin-a2 isoform is predominantly neuronal, with its strongest expression being in sensory ganglia. Analysis of dystonin in dorsal root ganglia (DRG) and of the DRG phenotype in dystonin mutant mice indicated that loss of the dystonin-a2 isoform, in particular, results in perikaryal abnormalities including disorganization of the rough ER. Analysis of other dystonin isoforms in cell culture indicated that they rely on different domains to dictate their localizations. Each of the dystonin isoforms may reorganize the cytoskeleton via direct interactions with actin filaments and microtubules. Our analysis indicates that a key cause of cell-intrinsic neuronal dysfunction and degeneration in dystonin mutant mice may occur as a result of aberrant cytoskeletal attachment to internal membranes, in particular the ER and nuclear envelope.
Keywords: Biology, Molecular.